Seasonal and Diurnal Variation on Tropospheric Scintillation at Ku-Band in Tropical Climate - Ibtihal Fawzi Elshami; Jafri Din (Institute of Advanced Engineering and Science, 2016)
Tropospheric scintillation is a rapid fluctuation of the received signal amplitude which can cause propagation impairments that affect satellite communication systems operating above 10 GHz. Scintillation data was collected in Equatorial Johor Bahru, Malaysia, based on a one-year Ku-band propagation measurement campaign, utilizing MEASAT-1 Satellite with an antenna elevation angle of 75.61°. This work concentrates on the probability density function (PDF) of diurnal variations of clear sky scintillation variance analyzed on an hourly basis. Besides, seasonal variation of scintillation amplitude has been presented in this paper. From the results, it is concluded that clear sky scintillation variance is likely to occur during morning and afternoon periods. Moreover, clear sky scintillation amplitude of the South-West monsoon shows a relatively higher comparing with others monsoon seasons. Hence, signal attenuation based on seasonal and diurnal information is of great interest for the system designers to appropriately design fade margin.Tropospheric scintillation is a rapid fluctuation of the received signal amplitude which can cause propagation impairments that affect satellite communication systems operating above 10 GHz. Scintillation data was collected in Equatorial Johor Bahru, Malaysia, based on a one-year Ku-band propagation measurement campaign, utilizing MEASAT-1 Satellite with an antenna elevation angle of 75.61°. This work concentrates on the probability density function (PDF) of diurnal variations of clear sky scintillation variance analyzed on an hourly basis. Besides, seasonal variation of scintillation amplitude has been presented in this paper. From the results, it is concluded that clear sky scintillation variance is likely to occur during morning and afternoon periods. Moreover, clear sky scintillation amplitude of the South-West monsoon shows a relatively higher comparing with others monsoon seasons. Hence, signal attenuation based on seasonal and diurnal information is of great interest for the system designers to appropriately design fade margin.